A Comparative Study on the Relationship Between the Quality of Space and Urban Activities in the Public Open Spaces - Uzgoren, Gokce; Erdonmez, Muyesser Ebru (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2017)
The quality of life of people in urban areas is a result of interaction of humans with the urban environment. Many studies show that open public spaces and the activities conducted in these areas are important urban environment factors that contribute to the quality of life. However, today, not only the quantity but also the quality of open public space tends to decrease. Along with this tendency, the quality in the urban space concept has become overemphasized. Density and diversity of urban space activities are conducted in public open spaces developed in parallel to the quality of space. Besides the environmental characteristics of the space; some indicators such as the density and diversity of urban space activities and the socio-economic status of users provides an important means of measuring the quality of space. In this study, the relationship between the quality of space in open public space and urban space activities has been revealed in the analysis conducted for the two parks-Sevgi Park and Azerbeycan Dostluk Park-located in Besiktas. Demonstrating how urban spaces are commodified by referring only to the physical structure without acknowledging their social and communal context and explaining the relationship between quality of space in urban spaces and urban space activities are the main objectives of these studies.
Keywords: Public open space; public space; urban space activities; quality of space; Architecture